KAJI EKSPERIMENTAL PENGARUH VARIASI DIAMETER NOZZEL DAN JUMLAH SUDU TERHADAP DAYA DAN EFFISIENSI PADA PROTOTYPE TURBIN PELTON DI LAB. FLUIDA - ., Supardi; Ridwan, Moh. (MEKANIKA: Jurnal Teknik Mesin, 2015)
Review of experimental effect of variations in the diameter of the nozzle and the amount of bucket on thepower and the efficiency on prototype pelton turbine in the Lab. Fluid. The aim of this study wants to know the effectof variations in the diameter of the nozzle and amount of the bucket to the power and efficiency of the existing peltonturbine prototype in the laboratory Fluid in the Pico-hydro scale. The steps in this research include the study ofliterature and field studies, designing, manufacturing of test equipment, testing, data analysis, and conclusions.Variation is done using nozzle diameter (dn) 6 mm and 9 mm, Î²2 at 165o, amount of bucket (Z) 12 units, 17 units,and 22 units. For the runner has a large diameter of 150 mm, while for the power plants or generators using spooland magnet on motorcycles. Results of this testing is the largest input power (Pin) at d 6 mm with a value of 46.81watts. The largest turbine power (Pt) and turbine efficiency (Î·t) at dnn = 6 mm with Z = 12 unit with value P= 40,34watt and Î·t =86,18 watt. The largest generator power (Pgen) at d = 6 mm with Z = 22 unit with value 9,6 watt,meanwhile for the largest generator efficiency (Î·genn) and the largest efficiency system (Î·sis) at d= 9 mm with Z = 22unit with value Î·gen = 54,24 % and Î·= 25,82 %.Keywords: Pelton Turbine, Bucket, Nozzle, Power and Efficiency